2021
DOI: 10.1016/j.ynstr.2021.100414
|View full text |Cite
|
Sign up to set email alerts
|

A voxel-level brain-wide association study of cortisol at 8 a.m.: Evidence from Cushing's disease

Abstract: Cortisol, the end product of the hypothalamic–pituitary–adrenal axis, regulates cognitive function and emotion processing. Cushing's disease, which is characterized by a unique excess of cortisol upon clinical diagnosis, serve as an excellent in vivo “hyperexpression” model to investigate the neurobiological mechanisms of cortisol in the human brain. Previous studies have shown the association between cortisol and functional connectivity within an a priori brain network. However, the who… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 79 publications
0
2
0
Order By: Relevance
“…Research progress on Cushing’s disease, which depends on static resting-state fMRI, revealed that patients with Cushing’s disease showed increased functional connectivity between the default mode network (DMN) and left lateral occipital cortex [ 2 ], and hippocampus [ 8 ]. Cortisol increase would induce connectivity changes within the DMN and salience network (SN) [ 9 ], and the DMN’s activity correlated with the morning cortisol level of patients with Cushing’s disease [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Research progress on Cushing’s disease, which depends on static resting-state fMRI, revealed that patients with Cushing’s disease showed increased functional connectivity between the default mode network (DMN) and left lateral occipital cortex [ 2 ], and hippocampus [ 8 ]. Cortisol increase would induce connectivity changes within the DMN and salience network (SN) [ 9 ], and the DMN’s activity correlated with the morning cortisol level of patients with Cushing’s disease [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…For example, the network-connectivity changes between SN and DMN [ 20 , 21 ], SN and CEN [ 22 ] corresponded to increased cortisol levels. Furthermore, our previous studies also identified that CD patients would show dysregulations of resting-state functional connectivity patterns with DMN [ 10 , 23 ]. Since CD patients also suffer from cognitive impairment and neuropsychological symptoms, including depression and anxiety, which DMN, SN, and CEN mainly modulate, we hypothesized that these three networks are critical to understanding Cushing’s disease and its comorbidity.…”
Section: Introductionmentioning
confidence: 99%